Beyond privacy vs. health: a justification analysis of the contact-tracing apps debate in the Netherlands - Siffels, Lotje Elizabeth (Ethics Inf Technol, 2020)
In the Netherlands, as in many other nations, the government has proposed the use of a contact-tracing app as a means of helping to contain the spread of the corona virus. The discussion about the use of such an app has mostly been framed in terms of a tradeoff between privacy and public health. This research statement presents an analysis of the Dutch public debate on Corona-apps by using the framework of Orders of Worth by Boltanski and Thévenot (1991). It argues that this framework can help us to move beyond the dichotomy of privacy vs. public health by recognizing a plurality of conceptions of the common good in the debate about contact-tracing apps. This statement presents six orders of worth present in the Dutch debate: civic, domestic, vitality, market, industrial and project, and argues that the identification of which common goods are at stake will contribute to discussions about the use of this technology from a standpoint with a richer ethical perspective.